Foreign Ownership Restrictions and Equity Price Premiums: What Drives the Demand for Cross-Border Investments? - Bailey, Warren; Chung, Y. Peter; Kang, Jun-koo (Journal of Financial and Quantitative Analysis, 1999)
Warren Bailey, Y. Peter Chung, Jun-koo Kang, Foreign Ownership Restrictions and Equity Price Premiums: What Drives the Demand for Cross-Border Investments?, The Journal of Financial and Quantitative Analysis, Vol. 34, No. 4 (Dec., 1999), pp. 489-511